Observation of risk factors for shoulder subluxation after stroke using ultrasonography to measure thickness of the supraspinatus muscle: a cross-sectional study - Qu, Yu; Shi, Xiue; Wang, Yongyong; Ji, Tiecheng; Chen, Lei; Yu, Suli; Huo, Ming (Frontiers in Neurology, 2025)
BackgroundThe prevention of shoulder subluxation, which is mainly caused by stroke, remains a challenge in rehabilitation treatment. While shoulder subluxation is a common problem after stroke, adequate objective predictors is lacking.AimThis study aimed to determine the acromion-greater tuberosity (A-GT) distance using ultrasound imaging in stroke patients, investigate the risk factors for shoulder subluxation after stroke, analyze the etiology of shoulder subluxation, and effectively prevent its occurrence.DesignCross-sectional study.SettingInpatient rehabilitation unit.PopulationOne hundred twenty-eight patients in our hospital between 2023 and 2024 with a confirmed diagnosis of stroke (age 59.1 ± 10.5 years; range 22–82 years; 82 males, 46 females; 100 cases of cerebral infarction and 28 of cerebral hemorrhage; 79 cases of left stroke and 49 of right; 82 patients in stage I, 19 in stage II; 11 in stage III, 9 in stage IV, and 7 in stage V).MethodsUltrasonographic variables (A-GT distance and supraspinatus thickness on the lesion side) were collected. The paired t-test was adopted to compare the A-GT distance and supraspinatus thickness between the paralyzed and non-paralyzed sides. Data (A-GT distance, supraspinatus thickness on the lesion side) were analyzed using one-way analysis of variance (ANOVA) and multiple comparison tests. Spearman’s correlation and multivariate linear regression were used to analyze the associations between the A-GT distance and specific clinical characteristics.ResultsThe A-GT distance was significantly increased in the paralyzed sides compared with the non-paralyzed sides (p < 0.01; paired t-test). The supraspinatus thickness was significantly reduced in the paralyzed compared sides with the non-paralyzed sides (p < 0.01; paired t-test). Significant differences were observed in A-GT distance between the sex, stroke type, and Brunnstrom stage groups (p < 0.01). Supraspinatus thickness on the lesion side showed significant differences between the sex, type of stroke, and lesion side groups (p < 0.01). A correlation between A-GT distance and supraspinatus thickness was also found (r = −0.474, p < 0.01). Based on the multivariate regression analysis, the independent risk factors for shoulder subluxation after stroke included type of stroke, supraspinatus thickness on the lesioned side, and Brunnstrom stage.ConclusionAcromio-greater tuberosity distance and reduced supraspinatus thickness on ultrasound, low Brunnstrom stage and history of cerebral hemorrhage were all found to be significant risk factors for shoulder subluxation after stroke.Clinical rehabilitation impactWe investigated the risk factors for shoulder subluxation after stroke, which may help physicians understand its mechanism and prevent its occurrence.